Teika The Life and Works of a Medieval Japanese Poet - Atkins, Paul S. (University of Hawaii Press, 2017)
Fujiwara no Teika (1162-1241) was born into an illustrious lineage of poets just as Japan's ancien régime was ceding authority to a new political order dominated by military power. Overcoming personal and political setbacks, Teika and his allies championed a new style of poetry that managed to innovate conceptually and linguistically within the narrow confines of the waka tradition and the limits of its thirty-one syllable form. Backed by powerful patrons, Teika emerged finally as the supreme arbiter of poetry in his time, serving as co-compiler of the eighth imperial anthology of waka, Shin Kokinshū (ca. 1210) and as solo compiler of the ninth.This first book-length study of Teika in English covers the most important and intriguing aspects of Teika's achievements and career, seeking the reasons behind Teika's fame and offering distinctive arguments about his oeuvre.